Penerapan Ilmu Tajwid Untuk Meningkatkan Pemahaman dan Kemampuan Membaca Al-Qur’an Anak-anak Di Tpa Ar-ruslan Desa Ciasihan - Yulia Agustina, Asiroch; Fahriansah; Thasya Amalia Putri; Rahmat Akbar; Rofa Rohmawati (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Learning the science of recitation and reading skills is a series of things taught in the Al-Qur'an Education Park (TPA) Ar-Ruslan Rt.02, Rw.04 Kampung Ranging Ciasihan Village, Kec. Pamijahan which aims to improve the skills of reading the Koran properly and correctly in accordance with the knowledge of tajwid. So the aim of this activity is to improve children's ability to read the Koran correctly and in accordance with their tajwid knowledge. With a good understanding of recitation, it is hoped that children will not only be able to read the Koran fluently, but also love it and make it an important part of their daily lives. The activity method used in this research is PAR (Participatory Action Research) based. Activities carried out in the community service program in Rangin village, Ciasihan village related to the application of the science of tajwid ran smoothly and obtained better results than before. This makes this activity have a positive impact on children, such as children gaining a new understanding of the rules for reading the Koran, thereby helping them improve their ability to read the Quran in tartil.